KAJIAN LITERATUR PENGELOLAAN OBAT DI RUMAH SAKIT: Literature Review on Drug Management in Hospitals - Irawan, Yanuar Hadi; Rostikarina, Nur Amalia; Rahmawati, Yunita (Forind Press, 2024)
Drug management is a managerial principle of hospitals, especially in terms of drug management in hospitals which aims to prevent stock out and stagnant stock. If this happens, it will result in inefficiency and become medically and economically bad. Because the quality of good drug services will improve the overall quality of hospital services. The design of this study is a literature review. The search for the articles discussed in this study uses several databases, including Google Scholar and ScienceDirect, with a time span of 2014 to 2024. The keywords used to search for the article are drug management, hospital, drug management. The type of article used is a research article. The collected articles are then re-selected using inclusion criteria, namely: 1) the purpose of the article is to analyze drug management in hospitals, 2) it is a cross-sectional research, and the exclusion criteria, namely 1) it is not a full-text article, 2) the article does not use Indonesian or English. The importance of drug management in pharmaceutical installations in achieving optimal health services in hospitals, so the drug management process needs to be supervised to find out the weaknesses and advantages in its operational implementation.